Generalized Higher Order (φ, η, ω, π, ρ, θ, m)-Invexities in Parametric Optimality Conditions for Discrete Minmax Fractional Programming - Ram U. Verma, (Journal of Basic & Applied Sciences, 2016)
First several new classes of higher order (φ, η, ω, π, ρ, θ, m)-invexities are introduced, and then a set of higher-order parametric necessary optimality conditions and several sets of higher order sufficient optimality conditions for a discrete minmax fractional programming problem applying various higher order (φ, η, ω, π, ρ, θ, m)-invexity constraints are established. The obtained results are new and generalize a wide range of results in the literature.